Risks & Challenges Program: Preventing behavioural addictions and dependencies - Dores, Artemisa R. (2022)
The literature supports the importance of prevention of psychoactive substances in college students, namely among first-year students. Although, few programs aim the intervention in behavioural addictions, such as gambling and gaming disorders. The purpose of this work is to present a Portuguese program, Risks & Challenges, and the experience of its implementation in the School of Health, Polytechnic of Porto.